HUBUNGAN MOTIVASI INTRINSIK TERHADAP PELAKSANAAN PEMBELAJARAN LANGSUNG DI FAKULTAS KEDOKTERAN HALU OLEO UNIVERSITAS KENDARI - Ashaeryanto Ashaeryanto; Satrio Wicaksono; Juminten Saimin; Rezki Fitrianti (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2019)
Self-Directed Learning (SDL) is a student-centered learning in which the process and experience of learning are individually regulated and controlled by the student. The implementation of SDL is an interaction of several aspects, including self-motivation, self-control, and self-monitoring skills. Students with strong motivation in the learning process will have more consistency in implementing the SDL. Inner self-motivation will give better impacts than that obtained from the outside. This study aimed to analyze the correlation of intrinsic motivation to SDL implementation in the Faculty of Medicine of Halu Oleo University. The study was quantitative research using a cross-sectional design. Subjects were 91 sophomores of the Faculty of Medicine of Halu Oleo University (UHO). Data were collected using a total sampling method. SDL implementation and intrinsic motivation were measured using Self-Directed Learning Readiness Scale (SDLRS) and Intrinsic Motivation Inventory (IMI) questionnaires, respectively. Data were statistically analyzed using Pearson’s correlation. Second-year of medical students of UHO showed a high intrinsic motivation and SDL implementation. Students with high intrinsic motivation were found to apply high implementation of SDL. Moreover, students with moderate intrinsic motivation also showed high implementation of SDL. There is a significant correlation between intrinsic motivation to SDL implementation among medical students of UHO. Further research is required to investigate other factors that affect the SDL implementation of medical students.